Healing from violence : Latino men's journey to a new masculinity - Welland, Christauria (Springer Pub., 2008)
Latinos are the fastest growing minority population in the United States. According to the 2000 Census, Latinos accounted for 12.5% of the US population, or 35.3 million residents. The influence of this large and growing demographic can be seen throughout every discipline, including social work, where numerous books on multicultural assessment, counseling, and research have begun to appear. One area of inquiry, however, that remains largely unexplored is domestic violence within Latino families. Although it appears that such violence occurs more frequently in Latino families than in Caucasian.